AB0454 Biological therapies survival in adults and juvenile onset arthritis. data from biobadaguay registry. (12th June 2018) - Avila-Pedretti, M.G.; Morel, Z.; Cabrera, N.; Cabrera-Villalba, S.; Acosta Colman, I.; Babak, P.; Melgarejo, P.; Elizaur, G.; Franco, M.; Delgadillo, P.; Cordovilla Montero, D.; Losanto, J.; et al.
Abstract : Background: Survival of biological therapies (BT) may be considered as an indicator of efficacy and safety of the drug. BT survival have been studied mainly in adult's patients, whereas only few studies have been focused on paediatric population to date. Objectives: To analyse and compare BT survival in adults and juvenile onset arthritis patients from BIOBADAGUAY registry. Methods: Patients with a chronic inflammatory arthritis enrolled in the Paraguayan-Uruguayan biological register (BIOBADAGUAY) between2015 and 2017 where included. For this study, patients were divided in two groups: 1. Adults with anychronic inflammatory arthritis and 2. Patients with juvenile idiopathic arthritis (JIA). To compare the groups according to BT, only the first biotherapy was considered. Survival analysis was performed using Kaplan-Meier estimators and proportional hazard regression model. First we analysed global BT survival in both groups; secondly we compare BT survival between groups. Results: From 778 BTs(etanercept n=184, adalimumab n=440, rituximab n=44, infliximab n=27, tocilizumab n=75, and others n=8), 556 where identify as first line BTs. Of these, only adalimumab and etanercept were included in the study due to sufficient number prescriptions in both groups for the analysis. We found a mean survival times for adults of 289 (±20.7 SD) weeks for etanercept and 287 (±8.6 SD) weeks for adalimumab. In JIA patients the mean survival were 243 (±26.0 SD) and 216 (±24.0 SD) weeks for etanercept and adalimumab respectively When comparing survival between groups, we found that JIA presented more discontinuation of BT when compare with adult patients (p=4.4 × 10–4, HR=0.51 [95%CI, 0.35–0.73]). Similar results were observed when analysing only etanercept (p=3.92 × 10–2; HR=0.50 [95% CI, 0.26–0.97]) or adalimumab (p=1.20 × 10–3; HR=0.48 [95% CI, 0.30–0.75])treatments. Then we analysed withdrawn motive in JIA patients, and found that remission was the principal reason of discontinuation in this group of patients. Finally, we stratified survival analysis by discontinuation according to adverse events, and found that JIA group presented a lower risk of discontinuation due to adverse events than adults (p=1.96 × 10–1; HR=2.18 [95% CI, 0.67–7.07]). Conclusions: In our study we have analysed mean BT survival between adults and JIA at the BIOBADAGUAY registry. When we compared both groups of patients it was observed that JIA patients presented more BT discontinuation but due to remission. Disclosure of Interest: None declared